Afterlives of Chinese Communism Political Concepts from Mao to Xi - Sorace, Christian; Franceschini, Ivan; Loubere, Nicholas (ANU Press, 2019)
Afterlives of Chinese Communism comprises essays from over fifty world- renowned scholars in the China field, from various disciplines and continents. It provides an indispensable guide for understanding how the Mao era continues to shape Chinese politics today. Each chapter discusses a concept or practice from the Mao period, what it attempted to do, and what has become of it since. The authors respond to the legacy of Maoism from numerous perspectives to consider what lessons Chinese communism can offer today, and whether there is a future for the egalitarian politics that it once promised.